2015
DOI: 10.1128/aac.04174-14
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Reduced Susceptibility to Tigecycline in Enterococcus faecium

Abstract: c Tigecycline (TIG) is approved for use for the treatment of complicated intra-abdominal infections, skin and skin structure infections, as well as pneumonia. Acquired resistance or reduced susceptibility to TIG has been observed in Gram-negative rods, has seldom been reported in Gram-positive organisms, and has not yet been reported in Enterococcus faecium. Using the serial passage method, in vitro mutant AusTig and in vitro mutants HMtig1 and HMtig2 with decreased TIG susceptibility (MICs, 0.25 g/ml) were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 27 publications
2
51
1
Order By: Relevance
“…While the data presented in Fig. 1 and those reported by Cattoir et al and Villa et al show a correlation between mutations in rpsJ and reduced TGC susceptibility, there has been no direct confirmation that mutations in rpsJ alone are able to significantly decrease susceptibility (8,9). To confirm the causal link between adaptive mutations in rpsJ to reduced TGC susceptibility, we used whole-genome sequencing to isolate a strain of E. faecalis S613 that contained only a mutation in rpsJ (10) Using comparative whole-genome sequencing between S613 and clones isolated from an adapted bioreactor population, a strain with a single mutation in rpsJ was identified, referred to here as S613(S10 R53Q-⌬54-57ATHK ).…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…While the data presented in Fig. 1 and those reported by Cattoir et al and Villa et al show a correlation between mutations in rpsJ and reduced TGC susceptibility, there has been no direct confirmation that mutations in rpsJ alone are able to significantly decrease susceptibility (8,9). To confirm the causal link between adaptive mutations in rpsJ to reduced TGC susceptibility, we used whole-genome sequencing to isolate a strain of E. faecalis S613 that contained only a mutation in rpsJ (10) Using comparative whole-genome sequencing between S613 and clones isolated from an adapted bioreactor population, a strain with a single mutation in rpsJ was identified, referred to here as S613(S10 R53Q-⌬54-57ATHK ).…”
Section: Resultscontrasting
confidence: 51%
“…Particularly, in the Gram-positive species, D60 of S10 was frequently mutated to a tyrosine. In this study, the S10 D60Y allele was independently isolated from 10 different populations, and the same allele was also identified in a previous study, where E. faecium was also adapted in vitro to TGC (8) (Fig. 1).…”
Section: H R L I D Qs T a E I V E T A K R T G A Q V R G P I P L P T Rmentioning
confidence: 81%
See 2 more Smart Citations
“…When we analyzed the region upstream of pbp5 in the draft genomes of TX82 A1 and 1.230.933 A1 , we found that the sequences in this area contain a series of gaps; however, alignments designed to close these gaps (the primers used are listed in Table S2), along with PCR and sequencing results, indicated a genetic environment similar to that in the subclade A1 strain Aus0004 (Table 2 and Fig. 2D), which is also highly resistant (MIC ϭ 256 g/ml, as described previously [24] and confirmed here). The region between psr and pbp5 in Aus0004 includes three different open reading frames (ORFs), ISEfm1, gnat, and hisJ, predicted to encode a transposase, an acetyltransferase, and a histidinol phosphate phosphatase, respectively (Fig.…”
Section: Resultsmentioning
confidence: 97%